BIAYA LOGISTIK DAN KELANCARAN PENGIRIMAN BARANG PADA GERAI BUKU - Nugraha, Yohanes; Mudjiono, Mudjiono; Edi, Dedeng Wahyu (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2016)
This study aims to determine the effect of the quality of human resources, the location of distribution centers and logistics costs in the effective delivery of goods from distribution centers to book stores.Â This survey respondents amounted to 78 employees in Scholastic Distribution Center and a few head or store manager Scholastic. The sampling technique using Simple Random Sampling and analysis techniques using path analysis (path analysis) with SPSS. The results showed the quality of human resources, the location of distribution centers and logistics costs directly affect the goodâs Â delivery effectivenes.